How can health, agriculture and economic policy actors work together to enhance the external food environment for fruit and vegetables? A qualitative policy analysis in India. (May 2018) - Thow, Anne Marie; Verma, Garima; Soni, Deepa; Soni, Divya; Beri, Deepti Kumar; Kumar, Poorvaja; Siegel, Karen R.; Shaikh, Nida; Khandelwal, Shweta
Highlights: Delivering diverse and high quality diets will require improving food environments. This qualitative policy analysis targeted policy coherence for fruit and vegetables in India. Public health actors can support agricultural/economic policy coherence for nutrition. Strategic framing and engagement with supply chain policy actors is key. Abstract: The benefits of fruit and vegetables are well established, particularly their role in preventing general micronutrient-deficiencies and chronic diseases. However, global food systems are not delivering diverse and high quality diets: healthy food is unavailable and too expensive for many. Creating food environments that foster consumer access to fruit and vegetables will require coordinated policy action across sectors, mostly outside of the health sector. The aim of this paper is to identify opportunities to strengthen food system policy for nutrition, through an analysis of the policies relevant to the external food environment for fruit and vegetables in India. We conducted interviews based on policy theory with 55 stakeholders from national and state level, from within government, research, private sector and non-government agencies, and from health, agriculture and economic sectors. Specific strategies identified in this study to improve consumers' external food environment for fruit and vegetables in India were: development of strategic Public-Private Partnerships to increase access to diverse expertise across the supply chain; linking health and economic/agricultural policy agendas; and strengthening surveillance of policy impacts on consumer access to fruit and vegetables. We also found that public health actors can play an important role in advocating for 'consumer oriented' fruit and vegetable supply policy. This study demonstrates the usefulness of 'policy learning'-oriented qualitative policy analysis in identifying 'points of entry' for food policy change, and extends understanding of political dynamics in engendering agricultural policy change for nutrition. Improving access to affordable fruit and vegetables is a global priority, and given common global food supply challenges, the findings from this study are also likely to be relevant for other low and middle income countries.